The Family as a Source of Aspiration for Family Members - Fitra Hadi Khaz; Erinaldi Erinaldi; Erika Yusmaini; Keke Ananta (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Family plays a strategic role as a source of aspiration for its members in shaping human resource quality and sustainable social development. However, various challenges remain, including limited understanding of the importance of emotional support, harmonious communication, and educational roles within the family. This community service activity aims to enhance public awareness and understanding of the family’s role as a source of aspiration for family members in Rimba Sekampung Village, Dumai City. A participatory approach was employed through socialization activities, interactive presentations, group discussions, and the development of informational media. The results indicate an improvement in community awareness and understanding of the importance of harmonious families, reflected in initial changes in attitudes and behaviors, increased support for family members’ education, and the emergence of community leaders and youth as local change agents. This activity also fostered collective awareness of the family’s role in human resource development, contributing to the potential for sustainable social transformation.